High thermal conductivity polyimide resin and polyimide film and preparation method and application thereof

By designing a new phosphorus-based dianhydride monomer and introducing long-chain alkyl diamines in the polyimide film, a local block structure is formed, and a film with low thermal conductivity, high flame retardancy and high mechanical strength is achieved, which is suitable for the coating of new energy power batteries.

CN119751868APending Publication Date: 2025-04-04TAIHU HUAQIANG TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411944787.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing polyimide film has low thermal conductivity, resulting in poor heat conduction, which can easily lead to local overheating and spontaneous combustion, limiting its widespread use in applications such as power batteries.

Method used

By designing a new phosphorus-based dianhydride monomer and introducing long-chain alkyl diamines, a local block structure is formed, which improves the thermal conductivity and flame retardant properties of the polyimide resin while enhancing its mechanical strength.

Benefits of technology

It realizes the high thermal conductivity, high flame retardancy and high mechanical strength of the polyimide film, and is suitable for the coating application of new energy power batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751868A_ABST
    Figure CN119751868A_ABST
Patent Text Reader

Abstract

The invention discloses a high thermal conductivity polyimide resin and a polyimide film and a preparation method and application thereof, and relates to the technical field of insulating thermal conductive materials. The invention designs a phosphorus-based dianhydride with a novel structure for synthesizing polyimide, introduces a phosphorus-based group into a polymer main chain, improves the flame retardant property of the material from the perspective of molecular design, and avoids the use of inorganic flame retardants, which results in a loss of material strength. At the same time, a long-chain alkyl diamine is used in combination with the flexibility of the phosphorus-based dianhydride itself, and a flexible part is introduced into the polymer chain segment, so as to facilitate a tighter rearrangement of the molecular chain and the formation of a crystal region, thereby introducing a heat conduction path at a microscopic level to improve its thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating thermally conductive materials, and in particular to a high thermally conductive polyimide resin and a polyimide film, and a preparation method and application thereof. Background Art

[0002] With the continuous development of the electronics industry, electronic devices are gradually developing towards high miniaturization, integration, multi-function and high frequency, which will inevitably generate heat concentration, seriously affecting the service life of electronic devices. Therefore, it is often necessary to rely on insulating coating materials to improve. In recent years, with the rise of the new energy electric vehicle industry, the insulation coating of power batteries has put forward new application requirements for the film material industry, because the heat dissipation of power batteries and their motors is a crucial link in the safety and stability of electric vehicles. The current method used in the industry is to wrap the power battery and motor with an insulating film and immerse it in a coolant. The coolant was mainly water-based in the early days, and was later changed to oily considering many factors. The main components are glycerin, ethylene glycol, additives and a small amount of water adsorbed during use.

[0003] At present, polyimide film is still one of the main materials used for power battery and motor coating. However, the intrinsic thermal conductivity of polyimide is very low, and there is no microscopic heat conduction path in the internal structure, which leads to high interface thermal resistance and poor thermal conductivity of the material itself, which is not conducive to the rapid conduction of heat and easily leads to local overheating or even spontaneous combustion, greatly limiting its wide application.

[0004] Therefore, in the prior art, the thermal conductivity of polyimide is generally improved by adding inorganic fillers, but this often leads to a serious loss of the mechanical properties of the film and a significant decrease in the service life, which is often not worth the cost.

[0005] Therefore, it is necessary to develop a new polyimide film with excellent thermal conductivity, and it is hoped that it will have both good mechanical strength and certain flame retardancy to meet the application under harsh conditions (such as when the power battery is working). Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a new type of polyimide resin and a preparation method thereof, and to prepare a polyimide film from the polyimide resin, so that the polyimide has the advantages of high thermal conductivity, high flame retardancy and high mechanical strength, and is more suitable for application in the field of new energy power battery coating.

[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0008] One of the objects of the present invention is to provide a polyimide resin, the structural formula of which is as follows:

[0009]

[0010] Among them, Ar 1 for

[0011] Ar 2 Selected from Any of the following:

[0012] R 1 for m = 3 to 12;

[0013] R 2 Selected from Any of the following:

[0014] P = 1 to 5;

[0015] X = 0.05-0.5;

[0016] n=6~100.

[0017] The second object of the present invention is to provide a method for preparing a polyimide resin, comprising the following steps:

[0018] (1) Phosphorus dianhydride, With H 2 NR 1 -NH 2 , H 2 NR 2 -NH 2 A condensation reaction occurs to obtain polyamic acid;

[0019] (2) The polyamic acid undergoes imidization reaction to obtain a polyimide resin.

[0020] The structural formula of the phosphorus dianhydride is as follows:

[0021]

[0022] The third object of the present invention is to provide a polyimide film made of the polyimide resin. The polyimide film can be prepared by a casting method, a spin coating method, a blade coating method, etc. commonly used in the art.

[0023] A fourth object of the present invention is to provide an application of the polyimide film in coating new energy power batteries.

[0024] The beneficial effects of the present invention are as follows: the present invention designs a phosphorus-based dianhydride of a novel structure for synthesizing polyimide, introduces a phosphorus-based group into a polymer main chain, improves the flame retardant properties of the material from a molecular design perspective, and avoids the use of inorganic flame retardants, which results in a loss of material strength; at the same time, a long-chain alkyl diamine is used in combination with the flexibility of the phosphorus-based dianhydride itself, and a flexible part is introduced into the polymer chain segment, so as to facilitate a tighter rearrangement of the molecular chain and the formation of a crystal region, thereby introducing a heat conduction path at a microscopic level to improve its thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the infrared spectrum of the polyimide resin prepared in Example 2. DETAILED DESCRIPTION

[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0027] The present invention provides a polyimide resin, the structural formula of which is as follows:

[0028]

[0029] Among them, Ar 1 for

[0030] Ar 2 Selected from Any of the following:

[0031] R 1 for m = 3 to 12;

[0032] R 2 Selected from Any of the following:

[0033] P = 1 to 5;

[0034] X = 0.05-0.5;

[0035] n=6~100.

[0036] Further, X = 0.05 to 0.3. In some preferred embodiments, X = 0.05 to 0.2.

[0037] Furthermore, n=15-75. In some preferred embodiments, n=20-50.

[0038] The present invention provides a method for preparing the polyimide resin, comprising the following steps:

[0039] (1) Phosphorus dianhydride, With H2 NR 1 -NH 2 , H 2 NR 2 -NH 2 A condensation reaction occurs to obtain polyamic acid;

[0040] (2) The polyamic acid undergoes imidization reaction to obtain a polyimide resin.

[0041] In order to further improve the thermal conductivity and insulation performance, the present invention also provides another method for preparing a polyimide resin, comprising the following steps:

[0042] (1) Phosphorus dianhydride, With H 2 NR 1 -NH 2 , H 2 NR 2 -NH 2 A condensation reaction occurs to obtain polyamic acid;

[0043] (2) mixing polyamic acid and boron nitride to obtain a polyamic acid / boron nitride composite;

[0044] (3) The polyamic acid / boron nitride complex undergoes imidization reaction to obtain a polyimide resin.

[0045] The structural formula of the phosphorus dianhydride is as follows:

[0046]

[0047] The preparation method of the phosphorus dianhydride comprises the following steps:

[0048] (1) phenyl phosphate undergoes a substitution reaction with 4-chloroanisole to obtain di(anisole)phenyl phosphate;

[0049] (2) di(anisole)phenyl phosphate is hydrolyzed to obtain bis(4-hydroxyphenyl)phenyl phosphate;

[0050] (3) Bis(4-hydroxyphenyl)phenyl phosphate undergoes a substitution reaction with 4-chloro-o-xylene to obtain bis(3,4-dimethyldiphenyl ether)phenyl phosphate;

[0051] (4) bis(3,4-dimethyldiphenyl ether)phenyl phosphate is oxidized to obtain bis(3,4-dicarboxydiphenyl ether)phenyl phosphate;

[0052] (5) The phosphorus-based dianhydride is obtained by condensation reaction of bis(3,4-dicarboxydiphenylether)phenyl phosphate.

[0053] The synthetic route is as follows:

[0054]

[0055] In step (1), the molar ratio of phenyl phosphate to 4-chloroanisole is 1:(2-2.2). A slightly excess amount of 4-chloroanisole can make the phenyl phosphate react as completely as possible.

[0056] In step (2), the hydrolysis reaction is carried out under acidic or alkaline conditions. Under acidic or alkaline conditions, the ester is hydrolyzed to generate phenol.

[0057] In step (3), the molar ratio of bis(4-hydroxyphenyl)phenyl phosphate to 4-chloro-o-xylene is 1:(2-2.2). A slightly excess amount of 4-chloro-o-xylene can make the bis(4-hydroxyphenyl)phenyl phosphate react as completely as possible.

[0058] In steps (1) and (3), the substitution reaction uses at least one of potassium carbonate, sodium carbonate, sodium acetate, triethylamine, pyridine, and N,N-diisopropylethylamine as an acid binding agent, but is not limited thereto. The acid binding agent neutralizes the hydrogen chloride generated by the substitution reaction and promotes the forward progress of the substitution reaction.

[0059] In step (4), the oxidation reaction uses at least one of potassium permanganate, potassium dichromate, and cobalt acetate as an oxidant, but is not limited thereto. Under the action of the oxidant, the methyl group on the benzene ring is oxidized to a carboxylic acid.

[0060] In step (5), the condensation reaction uses acetic anhydride as a dehydrating agent. Under the action of the dehydrating agent, the carboxylic acid molecules are dehydrated to form anhydrides.

[0061] The invention provides a polyimide film made of the polyimide resin.

[0062] The polyimide film can be prepared by a casting method, a spin coating method, a blade coating method, etc. commonly used in the art.

[0063] The present invention provides application of the polyimide film in coating new energy power batteries.

[0064] Example 1

[0065] Preparation of phosphorus dianhydride:

[0066] (1) Add phenyl phosphate (17.4 g, 100 mmol), 4-chloroanisole (28.4 g, 200 mmol), 150 g toluene and 21.2 g potassium carbonate powder into a reactor, heat to reflux and stir to react for 4 h. Stop the reaction, wash the reaction solution with water until it is neutral, take the organic phase, concentrate, let it stand, precipitate white crystals, filter and rinse with methanol, and dry to obtain di(anisole)phenyl phosphate with a yield of 56%. 1HNMR (DMSO) 3.71 (s, 6H, 2CH 3 ); 6.60-6.62 (d, 8H, 8CH); 7.3 (t, 4H, 4CH); 7.38 (t, 1H, 1CH).

[0067] (2) Add 25.6 g of di(anisole)phenyl phosphate, 350 mL of ethanol and 4 g of 10% dilute sulfuric acid solution to a reactor, heat to 40° C. and stir for 20 h. Stop the reaction, neutralize the reaction solution with tetramethylammonium hydroxide to neutrality, add water, stir, precipitate an off-white solid, filter, dissolve the residue with a mixture of ethanol / water (volume ratio 7:3) at room temperature, let stand for 24 h, filter, and dry to obtain bis(4-hydroxyphenyl)phenyl phosphate with a yield of 68%. 1 H NMR (DMSO) 4-5 (s, 2H, 2OH); 6.55-6.58 (d, 8H, 8CH); 7.28 (t, 4H, 4CH); 7.37 (t, 1H, 1CH).

[0068] (3) Under nitrogen protection, bis(4-hydroxyphenyl)phenyl phosphate (14.32 g, 40 mmol), 4-chloro-o-xylene (11.2 g, 80 mmol), 30 mL of m-cresol and 11.04 g of potassium carbonate were added to the reactor, and the mixture was heated to 150° C. and stirred for 4 h. The reaction was stopped, and water was added to the reaction solution, stirred, and a yellow solid was precipitated. The solid was filtered, and the residue was washed with water until neutral, and passed through a C18 chromatographic column to obtain bis(3,4-dimethyldiphenyl ether)phenyl phosphate with a yield of 34%. 1 H NMR (DMSO) 2.35 (m, 12H, 4CH 3 ); 6.7 (d, 4H, 4CH); 6.8 (d, 4H, 4CH); 6.64 (d, 4H, 4CH); 6.96 (d, 2H, 2CH); 7.34-7.37 (t, 5H, 5CH).

[0069] (4) Add 8 g of bis(3,4-dimethyldiphenyl ether)phenyl phosphate and 100 mL of 2% potassium permanganate aqueous solution to the reactor, heat to reflux and stir to react for 12 h. Stop the reaction, filter the reaction solution, wash with water, and dry to obtain bis(3,4-dicarboxydiphenyl ether)phenyl phosphate with a yield of 81%. 1 H NMR (DMSO) 11.8 (m, 4H, 4COOH); 6.76 (d, 4H, 4CH); 6.89 (d, 4H, 4CH); 7.54 (d, 2H, 2CH); 8.02 (s, 2H, 2CH); 8.32 (d, 2H, 2CH); 7.34-7.37 (t, 5H, 5CH).

[0070] (5) Add 7 g of bis(3,4-dicarboxydiphenyl ether)phenyl phosphate and 50 mL of acetic anhydride to the reactor, heat to reflux and stir to react for 8 h. Stop the reaction, add methanol to the reaction solution, stir, precipitate solids, filter, wash the filter residue with methanol, and dry to obtain phosphorus dianhydride with a yield of 84%. 1 H NMR (DMSO) 6.77 (d, 4H, 4CH); 6.88 (d, 4H, 4CH); 7.47 (d, 2H, 2CH); 8.0 (s, 2H, 2CH); 8.32 (d, 2H, 2CH); 7.34-7.37 (t, 5H, 5CH).

[0071] Example 2

[0072] Under nitrogen protection, add the phosphorus dianhydride (58.5g, 0.09mol) and 1700mL DMF prepared in Example 1 to the reactor, add hexamethylenediamine (20.88g, 0.18mol) after complete dissolution, stir and react at room temperature for 8h, then add 4,4′-diaminodiphenyl ether (164g, 0.82mol), add pyromellitic anhydride (198.4g, 0.91mol) after complete dissolution, stir and react at room temperature for 20h to obtain a polyamic acid solution. Add 44.5g of boron nitride powder to the polyamic acid solution, stir and disperse vigorously to obtain a polyamic acid / boron nitride composite solution, scrape and film after the solution is defoamed, dry, and finally perform imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0073] Example 3

[0074] Under nitrogen protection, the phosphorus dianhydride (58.5 g, 0.09 mol) prepared in Example 1 and 1700 mL of DMF were added to the reactor, and after complete dissolution, 1,12-dodecanediamine (36.05 g, 0.18 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (164 g, 0.82 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 10 h to obtain a polyamic acid solution.

[0075] Add 46 g of boron nitride powder to the polyamic acid solution, stir vigorously to disperse, and obtain a polyamic acid / boron nitride composite solution. After the solution is defoamed, it is coated into a film, dried, and finally subjected to imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0076] Example 4

[0077] Under nitrogen protection, the phosphorus dianhydride (58.5 g, 0.09 mol) prepared in Example 1 and 1700 mL of DMF were added to the reactor, and after complete dissolution, 1,3-propylenediamine (13.3 g, 0.18 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (164 g, 0.82 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 10 h to obtain a polyamic acid solution.

[0078] Add 43.8 g of boron nitride powder to the polyamic acid solution, stir vigorously to disperse, and obtain a polyamic acid / boron nitride composite solution. After the solution is defoamed, it is coated into a film, dried, and finally subjected to imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0079] Example 5

[0080] Under nitrogen protection, the phosphorus dianhydride (58.5 g, 0.09 mol) prepared in Example 1 and 1700 mL of DMF were added to the reactor, and after complete dissolution, hexamethylenediamine (12.53 g, 0.108 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (178.4 g, 0.892 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 20 h to obtain a polyamic acid solution.

[0081] Add 44.8 g of boron nitride powder to the polyamic acid solution, stir vigorously to disperse, and obtain a polyamic acid / boron nitride composite solution. After the solution is defoamed, it is coated into a film, dried, and finally subjected to imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0082] Example 6

[0083] Under nitrogen protection, the phosphorus dianhydride (58.5 g, 0.09 mol) prepared in Example 1 and 1700 mL of DMF were added to the reactor, and after complete dissolution, hexamethylenediamine (12.53 g, 0.108 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (178.4 g, 0.892 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 20 h to obtain a polyamic acid solution.

[0084] Add 89.6 g of boron nitride powder to the polyamic acid solution, stir vigorously to disperse, and obtain a polyamic acid / boron nitride composite solution. After the solution is defoamed, it is coated into a film, dried, and finally subjected to imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0085] Example 7

[0086] Under nitrogen protection, the phosphorus dianhydride (58.5 g, 0.09 mol) prepared in Example 1 and 1700 mL of DMF were added to the reactor, and after complete dissolution, hexamethylenediamine (12.53 g, 0.108 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (178.4 g, 0.892 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 20 h to obtain a polyamic acid solution.

[0087] Add 134.4 g of boron nitride powder to the polyamic acid solution, stir vigorously to disperse, and obtain a polyamic acid / boron nitride composite solution. After the solution is defoamed, it is coated into a film, dried, and finally subjected to imidization reaction (120℃ / 60min, 175℃ / 15min, 250℃ / 15min, 320℃ / 10min) to obtain a polyimide film.

[0088] Comparative Example 1

[0089] Under nitrogen protection, pyromellitic anhydride (19.6 g, 0.09 mol) and 1700 mL of DMF were added to the reactor. After complete dissolution, hexamethylenediamine (12.53 g, 0.108 mol) was added, and the mixture was stirred at room temperature for 8 h. Then, 4,4′-diaminodiphenyl ether (164 g, 0.82 mol) was added, and after complete dissolution, pyromellitic anhydride (198.4 g, 0.91 mol) was added, and the mixture was stirred at room temperature for 20 h to obtain a polyamic acid solution.

[0090] 40.6 g of boron nitride powder was added to the polyamic acid solution, and the mixture was vigorously stirred and dispersed to obtain a polyamic acid / boron nitride composite solution. After the solution was defoamed, it was coated into a film, dried, and a polyimide film was obtained through an imidization reaction.

[0091] Comparative Example 2

[0092] The method of Example 5 was followed, except that the molar ratio of phosphorus dianhydride to hexamethylenediamine was adjusted from 1:1.2 to 1:1.6. As a result, the solubility of the polymer decreased due to its high crystallinity, and the polymer precipitated, and the reaction was terminated.

[0093] The thermal conductivity, mechanical properties and flame retardancy of the polyimide films obtained in the above examples and comparative examples were tested. The test results are shown in Table 1.

[0094] Thermal conductivity test: According to standard ASTM E1461, German NETZSCH thermal conductivity tester LFA447.

[0095] Mechanical properties test: in accordance with standard GB / T 1040-1998.

[0096] Limiting oxygen index test: in accordance with standard GB / T 2406.1-2008; the critical volume fraction of oxygen in the mixed gas is the LOI value.

[0097] Molecular weight test: Agilent 1100 Series high performance liquid chromatograph, polystyrene as standard, injection volume 50.000 μL, DMF as mobile phase, flow rate 1.000 mL / min, column temperature 25°C; weigh 0.0500 g of polyimide resin and dissolve it in 2.00 mL of chromatographically pure DMF, filter it with a 0.45 μm filter membrane after it is completely dissolved, and then measure its molecular weight with high performance liquid chromatography.

[0098] Table 1

[0099]

[0100] As can be seen from Table 1, the present invention improves the flame retardancy of the polyimide resin by using a novel phosphorus dianhydride monomer and introducing aliphatic diamine to form a local block, and also improves the mechanical strength and thermal conductivity of the polyimide resin by forming a crystalline region.

[0101] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A polyimide resin, characterized in that: The structural formula of the polyimide resin is as follows: Where Ar1 is Ar2 is selected from Any of the following: R1 is m = 3 to 12; R2 is selected from Any of the following: P=1~5; X=0.05~0.5; n=6~100。 2. The polyimide resin according to claim 1, characterized in that: X=0.05-0.3; preferably, X=0.05-0.

2.

3. The polyimide resin according to claim 1, characterized in that: n=15-75; preferably, n=20-50.

4. The method for preparing a polyimide resin according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Phosphorus dianhydride, Condensation reaction with H2N-R1-NH2 and H2N-R2-NH2 produces polyamic acid; (2) The polyamic acid undergoes imidization reaction to obtain a polyimide resin.

5. The method for preparing a polyimide resin according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Phosphorus dianhydride, Condensation reaction with H2N-R1-NH2 and H2N-R2-NH2 produces polyamic acid; (2) mixing polyamic acid and boron nitride to obtain a polyamic acid / boron nitride composite; (3) The polyamic acid / boron nitride complex undergoes imidization reaction to obtain a polyimide resin.

6. The preparation method according to claim 4 or 5, characterized in that: The structural formula of the phosphorus dianhydride is as follows:

7. The preparation method according to claim 6, characterized in that: The preparation method of the phosphorus dianhydride comprises the following steps: (1) phenyl phosphate undergoes a substitution reaction with 4-chloroanisole to obtain di(anisole)phenyl phosphate; (2) di(anisole)phenyl phosphate is hydrolyzed to obtain bis(4-hydroxyphenyl)phenyl phosphate; (3) Bis(4-hydroxyphenyl)phenyl phosphate undergoes a substitution reaction with 4-chloro-o-xylene to obtain bis(3,4-dimethyldiphenyl ether)phenyl phosphate; (4) bis(3,4-dimethyldiphenyl ether)phenyl phosphate is oxidized to obtain bis(3,4-dicarboxydiphenyl ether)phenyl phosphate; (5) The phosphorus-based dianhydride is obtained by condensation reaction of bis(3,4-dicarboxydiphenylether)phenyl phosphate.

8. The preparation method according to claim 7, characterized in that: In step (1), the molar ratio of the phenyl phosphate to 4-chloroanisole is 1:(2-2.2); In step (2), the hydrolysis reaction is carried out under acidic or alkaline conditions; In step (3), the molar ratio of bis(4-hydroxyphenyl)phenyl phosphate to 4-chloro-o-xylene is 1:(2-2.2); In steps (1) and (3), the substitution reaction uses at least one of potassium carbonate, sodium carbonate, sodium acetate, triethylamine, pyridine, and N,N-diisopropylethylamine as an acid binding agent; In step (4), the oxidation reaction uses at least one of potassium permanganate, potassium dichromate, and cobalt acetate as an oxidant; In step (5), acetic anhydride is used as a dehydrating agent in the condensation reaction.

9. A polyimide film, made from the polyimide resin according to any one of claims 1 to 3 or the polyimide resin prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the polyimide film according to claim 9 in coating new energy power batteries.

Citation Information

Cited By

  • High-thermal-conductivity colored polyimide composite film and preparation method thereof

    CN120757822A

  • Highly heat-conductive color polyimide composite film and preparation method thereof

    CN120757822B